Characterization and bioremediation potential of nickel-resistant endophytic bacteria isolated from the wetland plant Tamarix chinensis. Issue 12 (18th June 2020) - Chen, Jun; Li, Na; Han, Sheng; Sun, Yuankai; Wang, Lili; Qu, Zhili; Dai, Meixue; Zhao, Guoyan
Abstract: Wetlands have been proposed as a sink for pollutants such as heavy metals. Wetland plants play a significant role in the phytoremediation of heavy metals. Here, we isolated and characterized three novel nickel (Ni)-resistant endophytic bacteria (NiEB) from the wetland plant Tamarix chinensis . The NiEB were identified as Stenotrophomonas sp. S20, Pseudomonas sp. P21 and Sphingobium sp. S42. All isolates tolerated 50 mg L −1 Ni, with isolates S20 and P21 being more tolerant to Ni at up to 400 mg L −1 . Moreover, isolate S42 removed 33.7% of nickel sulfate from the water by forming white precipitates. The three isolates exhibited different plant growth-promoting (PGP) traits related to the production of indole acetic acid (IAA), siderophores and 1-aminocyclopropane-1-carboxylate (ACC) deaminase. Phytotoxicity studies revealed that the growth of the wetland plants in a high Ni concentration (200 mg L −1 ) recovered after co-incubation with isolate S42. Overall, this study presents the first report of NiEB isolation from wetland plants and provides novel insights into the diverse functions of endophytic bacteria in a plant host with the potential to improve Ni phytoremediation. Abstract : Three novel Ni-resistant endophytic bacteria were characterized from wetland plant Tamarix chinensis with Ni-removal and plant growth-promoting traits.